Greece : First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2010)
The recession is unfolding in line with expectations. Inflation is higher than expected from indirect tax hikes. The key challenges remain restoring fiscal sustainability, safeguarding financial sector stability, and boosting competitiveness-and hence growth and employment. Staff and authorities agreed that nominal growth will be somewhat higher than originally anticipated. The government will facilitate private investment including through the privatization program. Stronger public financial management and especially tax administration are needed to mitigate risks. Advancing tax administration reform is a crucial priority to limit risks.